2002
DOI: 10.1097/00005053-200210000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Adult Attachment, and Recollections of Parental Caring During Childhood

Abstract: The onset and course of depressive symptoms are influenced by a variety of interpersonal factors. Attachment theory provides a developmental framework for understanding the relationship between depressive symptoms and insecure attachment to one's parents and current romantic partner. The present study examined attachment theory for understanding depression and marital adjustment among 84 psychiatric inpatients diagnosed with major depressive disorder. Participants completed a diagnostic interview and self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
1
10
0
3
Order By: Relevance
“…Given anxiously and avoidantly attached individuals' idiosyncratic difficulties establishing a healthy balance between autonomy and closeness (Mikulincer, 2006), they are more likely to experience lower levels of relationship satisfaction (Mikulincer & Shaver, 2007). Such findings correspond with a large body of research consistently yielding significant inverse associations between attachment insecurity and couple satisfaction (e.g., DiFilippo & Overholser, 2002;Elizur & Mintzer, 2001;Rholes, Simpson, & Friedman, 2006;Ridge & Feeney, 1998;Roberts & Noller, 1997;Treboux, Crowell, & Waters, 2004).…”
Section: Attachment and Couple Satisfactionsupporting
confidence: 87%
“…Given anxiously and avoidantly attached individuals' idiosyncratic difficulties establishing a healthy balance between autonomy and closeness (Mikulincer, 2006), they are more likely to experience lower levels of relationship satisfaction (Mikulincer & Shaver, 2007). Such findings correspond with a large body of research consistently yielding significant inverse associations between attachment insecurity and couple satisfaction (e.g., DiFilippo & Overholser, 2002;Elizur & Mintzer, 2001;Rholes, Simpson, & Friedman, 2006;Ridge & Feeney, 1998;Roberts & Noller, 1997;Treboux, Crowell, & Waters, 2004).…”
Section: Attachment and Couple Satisfactionsupporting
confidence: 87%
“…Parental nurturing behavior has been considered a strong candidate in affecting child's social attachment (e.g. Bowlby 1988), although not all studies have provided supporting evidence for this relationship (Difilippo & Overholser 2002; Lopez et al 2000; Parker et al 1992). Studies of child temperament have shown how children with different temperaments are differentially susceptible to parenting and quality of child care (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all studies have observed consistent associations between parental care and later attachment behaviors. In many studies, the effects have been small (Donnellan et al 2005; Lopez et al 2000) or completely absent (Difilippo & Overholser 2002; Lopez et al 2000; Parker et al 1992). While these inconsistencies may be related to the wide range of definitions and measures used to evaluate both parental care and social attachment, it is also possible that there is heterogeneity in how individuals respond to parental care.…”
mentioning
confidence: 99%
“…Additionally, studies have repeatedly demonstrated that PBI scores do not appear to be significantly influenced by mood state (e.g. Difilippo & Overholser, 2002; Tait, Birchwood, & Trower, 2004).…”
Section: Methodsmentioning
confidence: 99%